FROM 'LAND TENURE FORUMS' TO 'HERITAGE MANAGEMENT' - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
In southern Senegal, anti-salination dams have allowed the re-development of the River Farankounda valley, one of the tributaries of the River Casamance. They have also led to renewed tension over land tenure, and to an original community...